Predicting Hepatic Encephalopathy-Related Hospitalizations Using a Composite Assessment of Cognitive Impairment and Frailty in 355 Patients With Cirrhosis. (October 2018) - Ney, Michael; Tangri, Navdeep; Dobbs, Bonnie; Bajaj, Jasmohan; Rolfson, Darryl; Ma, Mang; Ferguson, Thomas; Bhardwaj, Param; Bailey, Robert; Abraldes, Juan; Tandon, Puneeta
Abstract Introduction Hepatic encephalopathy (HE) is the most common potentially modifiable reason for admission in patients with cirrhosis. Cognitive and physical components of frailty have pathophysiologic rationale as risk factors for HE. We aimed to assess the utility of a composite score (MoCA–CFS) developed using the Montreal Cognitive Assessment (MoCA) and the Clinical Frailty Scale (CFS) for predicting HE admissions within 6 months. Methods Consecutive adult patients with cirrhosis were followed for 6 months or until death/transplant. Patients with overt HE and dementia were excluded. Primary outcome was the prediction of HE-related admissions at 6 months. Results A total of 355 patients were included; mean age 55.9 ± 9.6; 62.5% male; Hepatitis C and alcohol etiology in 64%. Thirty-six percent of patients had cognitive impairment according to the MoCA (≤24) and 14% were frail on the CFS (>4). The MoCA–CFS independently predicted HE hospitalization within 6 months, a MoCA–CFS score of 1 and 2 respectively increasing the odds of hospitalization by 3.3 (95% CI:1.5–7.7) and 5.7 (95% CI:1.9–17.3). HRQoL decreased with increasing MoCA–CFS. Depression and older age were independent predictors of a low MoCA. Conclusions Cognitive and physical frailty are common in patients with cirrhosis. In addition to being an independent predictor of HE admissions within 6 months, the MoCA-CFS composite score predicts impaired HRQoL and all-cause admissions within 6 months. These data support the predictive value of a "multidimensional" frailty tool for the prediction of adverse clinical outcomes and highlight the potential for a multi-faceted approach to therapy targeting cognitive impairment, physical frailty and depression.